From Disparity to Opportunity: Racial Differences in Internet Access and Health App Usage Among Older Informal Caregivers. - Wang, Kun; Dong, Yanjun; Zeng, Xiaoyi; Johnson, Charles; Ruggiano, Nicole; Clay, Olivio J. (Journal of Applied Gerontology, 2026)
This study examines Black–White disparities in Internet and smart device usage among older informal caregivers. Using pooled data from the 2017–2020 Health Information National Trends Survey (N = 1,005, aged 50+), we employed logistic regression to assess racial disparities in Internet use, social media engagement, and smart device ownership. Among smart device owners, we further examined different health-related app usage. Older black caregivers were significantly less likely than White caregivers to use the Internet (OR = 0.23, 95% CI = [0.11, 0.46]). However, among smart device owners, Black caregivers were more likely to use apps for health-related goals (OR = 2.42, 95% CI = [1.42, 4.12]) and decision-making (OR = 1.87, 95% CI = [1.11, 3.15]). Despite lower Internet access, Black caregivers demonstrate high engagement with digital health tools when access is available. Bridging the digital divide in underserved communities may improve equity and expand support for older caregivers.